PENGARUH PROFITABILITAS, LEVERAGE DAN STATUS PERUSAHAAN TERHADAP PENGUNGKAPAN LAPORAN KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2017-2019 - Shokib Rohmatulloh; Junaidi Junaidi; Afifudin Afifudin (Universitas Islam Malang, 2022)
This study aims to analyze the effect of Profitability, Leverage and Company Status on Financial Statement Disclosure. The sampling technique used in this research is to use the purposive sampling method with a total sample of 61 companies. The data was obtained through the official website of the Indonesian Stock Exchange from 2017-2019. The analytical technique used is descriptive statistical test, normality test, classical assumption test, multiple linear regression analysis and hypothesis testing with a significance level (α) of 0.005. The results of this study indicate that Profitability and Leverage have an effect on Disclosure of Financial Statements while Company Status has no effect on Disclosure of Financial Statements.Keywords: Profitability, Leverage, Company Status, and Financial Statements Disclosure.